Strategi Pemerintah Desa Dalam Pembangunan Fisik di Desa Aji Kuning Kecamatan Sebatik Tengah Kabupaten Nunukan - Rusdin; Jauchar; Nur Hasanah (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2021)
This study aims to determine the strategy undertaken by the Village Government of Aji Kuning in carrying out physical development. The research method used in the preparation of this thesis is a qualitative descriptive research method and is a field research using data obtained from observation, interviews, documentation and secondary data. The results of the study show that in carrying out physical development the village has several strategies, namely in formulating a vision and mission through a bottom up approach, namely prioritizing community interests, development planning that looks at environmental aspects so that in development it also prioritizes natural disaster management, guarantees apparatus capacity by increasing capacity village apparatus through training and technical guidance, motivating the apparatus so that the competition that occurs can be positive in order to improve the work ethic and establish good communication and coordination with internal and external parties. From the several strategies carried out, it can be seen that the pattern of development strategy used is the pattern of integrated rural development. In the process of implementing development, there are also supporting and inhibiting factors. The supporting factors are the high participation of the village community in the stages of planning, implementation, up to monitoring the evaluation of the results of physical development and the existence of an attitude of transparency on the part of the Village Government in terms of implementing physical development. The inhibiting factor is the lack of human resources, namely technical experts and also the difficulty in obtaining heavy equipment assistance in supporting the development implementation process.